A hot-melt adhesive film with self-repairing ability and preparation method thereof

By designing poly(etheramine-siloxane-imine) block copolymers and utilizing multiple action mechanisms, a hot-melt adhesive film with efficient self-healing, excellent toughness and bonding properties was prepared, solving the problems of existing adhesive films. The problem of loss of toughness and adhesion during the process of improving self-healing function.

CN118956336BActive Publication Date: 2025-01-21COMO (SHANGHAI) NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411442632.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

While improving the self-healing function, the existing hot melt adhesive films have problems such as low repair efficiency, uneven mixing of functional components with the substrate, and damaged film toughness and adhesion.

Method used

By designing poly(etheramine-siloxane-imine) block copolymers and utilizing multiple action mechanisms such as amide bonds, hydrogen bonds, siloxane units and disulfide bonds, a hot-melt adhesive with self-healing function was prepared membrane. The adhesive film is synthesized through a one-step method using amide bond-containing dianhydride monomer, polyetheramine, siloxane diamine and disulfide bond diamine as raw materials.

Benefits of technology

The adhesive film can be efficiently self-healed at room temperature, with a repair efficiency of 85~90%, while maintaining excellent toughness and bonding properties, and is suitable for bonding metal and polymer surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

This invention relates to a self-healing hot-melt adhesive film and its preparation method. The film is prepared from a poly(etheramine-siloxane-imine) block copolymer, containing polyetheramine, polysiloxane, and polyimide segments in its molecular chain. Amide bonds are also introduced into the rigid polyimide segments. The abundant hydrogen bonding between the amide groups and polyetheramine segments, along with the siloxane units, gives this type of film excellent adhesion to polymers, metals, and other materials. At room temperature, the adhesion strength to metals (taking copper foil as an example) reaches 9-15 MPa, and the adhesion strength to polymer surfaces reaches 6-10 MPa. Therefore, the hot-melt adhesive film proposed in this invention possesses excellent adhesion performance, room-temperature self-healing capability, and good mechanical properties, showing significant application prospects in semiconductor packaging, thermal interface management, and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced functional materials, and in particular relates to a hot-melt adhesive film with self-repairing ability and a preparation method thereof. Background Art

[0002] Hot-melt adhesive film is a kind of adhesive film product that can use the hot melt method to melt the adhesive and apply it on the surface of the substrate. This type of material is usually a solid film at room temperature. It has the advantages of high bonding strength, convenient construction and low cost. It has been widely used in semiconductor packaging, flexible copper clad laminates, thermal interface materials and other fields.

[0003] Common hot melt adhesive films include thermoplastic polyurethane (TPU), ethylene-vinyl acetate copolymer (EVA) hot melt adhesive film, polyamide (PA) hot melt adhesive film and polymethylsiloxane (PDMS) hot melt adhesive film. With the continuous advancement of science and technology, various fields have put forward higher requirements for such materials. For example, in order to improve the safe service performance of adhesive film materials, in addition to excellent bonding performance, the fields of thermal interface materials and semiconductor packaging also expect such adhesive films to have self-healing functions, so that the bonding interface can heal spontaneously after being damaged by impact (such as force, heat, etc.), thereby improving the service safety of the bonding layer. For example, the disclosed invention patent (CN 202210912188.1) reported a method for preparing a TPU film with self-healing function by blending and adding self-healing supramolecular compounds. When the mass of the self-healing supramolecular compound is controlled to be 5-8 parts, the self-healing efficiency of the film reaches 81%-85%; the disclosed invention patent (CN 202011159373.5) reported a method for preparing a PDMS material with self-healing function by blending and adding O-acylisourea intermediates in epoxy-functionalized PDMS material. The above-mentioned method of physical blending can effectively give the traditional film a self-healing function, but there are often problems such as low repair efficiency, uneven mixing of functional components and substrates, and impaired toughness and adhesion of the film. Therefore, how to prepare an intrinsic hot-melt film with both room temperature self-healing function and excellent toughness and adhesion through macromolecular structure design and multiple action mechanisms is a key prerequisite for expanding the application field of such materials and meeting the increasingly demanding needs of different fields. Summary of the invention

[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a hot-melt adhesive film having room temperature self-healing function, excellent toughness and outstanding bonding ability and a preparation method thereof.

[0005] In the first aspect, a hot-melt adhesive film with self-healing function is provided, wherein the hot-melt adhesive film is prepared from a poly(etheramine-siloxane-imine) block copolymer, wherein the poly(etheramine-siloxane-imine) block copolymer uses a dianhydride monomer containing an amide bond, a diamine containing a polyether unit (polyetheramine), a diamine containing a siloxane unit, and a diamine containing a disulfide bond as raw materials, and its molecular chain comprises polyetheramine, polysiloxane, and polyimide segments; wherein the abundant hydrogen bonding between the polyetheramine segments and the large number of disulfide bonds between the polyimide segments give the adhesive film excellent room temperature healing ability; in addition, the microphase separation structure formed between the flexible polyetheramine, polysiloxane, and rigid polyimide segments gives the adhesive film outstanding toughness, and the hydrogen bonds and siloxane units make this type of adhesive film have excellent adhesion to materials such as polymers and metals.

[0006] Preferably, the dianhydride monomer containing an amide bond is N,N'-(2,2-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxyamide) (abbreviated as: TA-TFMB), and its structure is shown below:

[0007] .

[0008] Preferably, the chemical structures of the diamine containing polyether units, the diamine containing siloxane units and the diamine containing disulfide bond units are respectively: amino-terminated polyoxypropylene ether, amino-terminated polydimethylsiloxane-bisamino (PDMS-2NH2) and diamine 4,4'-diaminodiphenyl disulfide containing disulfide bonds, and the corresponding structures are shown below:

[0009] , , .

[0010] Preferably, the molecular weight of the diamine containing siloxane units is 500-5000, and the molecular weight of the diamine containing polyether units is 230-4000; more preferably, the molecular weight of the diamine containing siloxane units is 2500.

[0011] Preferably, the molar content of the polyimide segment in the block copolymer is 10-30 mol%, the polyetheramine and polysiloxane segments are in equimolar amounts, and the total molar fraction of the two segments is 70-90 mol%.

[0012] Preferably, the hot-melt adhesive film can self-repair at room temperature for 6 hours after being broken, and the tensile strength repair efficiency reaches 85-90%.

[0013] Preferably, the hot melt adhesive film has a bonding strength of 9 to 15 MPa to metal surfaces and a bonding strength of 6 to 10 MPa to polymer surfaces at room temperature.

[0014] Preferably, the above-mentioned metal is copper foil.

[0015] Preferably, the hot-melt adhesive film can be melt-processed at 80-150°C.

[0016] In the second aspect, the preparation method of the above-mentioned hot-melt adhesive film with self-healing function includes: using a dianhydride monomer containing an amide bond, a diamine containing a polyether unit (polyether amine), a diamine containing a siloxane unit and a diamine containing a disulfide bond as raw materials, and synthesizing them by a one-step method under the action of a solvent and a catalyst.

[0017] Wherein, the solvent includes any one or both of N-methyl-pyrrolidone (NMP) or m-cresol;

[0018] Wherein, the catalyst includes any one or both of pyridine and isoquinoline.

[0019] In a third aspect, the specific steps of the above-mentioned preparation method include:

[0020] S1, dissolving the dianhydride containing amide units in a solvent to obtain a transparent dianhydride solution;

[0021] S2, gradually adding a diamine containing a polyether unit, a diamine containing a siloxane unit and a diamine containing a disulfide bond unit to the above dianhydride solution, and after all the diamine monomers are dissolved, stirring at room temperature to obtain a precursor solution;

[0022] S3, adding a catalyst to the precursor solution, and heating it to 100-200°C, reacting at this temperature for 15-20 h, and finally obtaining a film solution;

[0023] S4, coating the above adhesive film solution on the surface of the substrate, and preparing a hot-melt adhesive film after drying.

[0024] Preferably, nitrogen or inert gas is introduced in steps S1 and S2 for protection;

[0025] Preferably, stirring at room temperature in step S2 for 18 to 24 h;

[0026] Preferably, in step S3, the reaction solution is first heated to 100-120° C., reacted at this temperature for 5-8 hours, and the reaction system is further heated to 180-200° C., and reacted at this temperature for 10-12 hours;

[0027] Preferably, in step S4, the adhesive film solution is coated on the surface of the substrate by a doctor blade coating or a casting process;

[0028] Preferably, the substrate in step S4 is a glass plate;

[0029] Preferably, the drying process in step S4 refers to a drying process at 120° C. for 8 to 10 hours;

[0030] Preferably, the total mass fraction of reactants in step S2 is 15-25 wt%;

[0031] Preferably, the amount of catalyst used in step S3 is 3-5 wt% of the reactant mass.

[0032] In a fourth aspect, the above-mentioned hot-melt adhesive film with self-repairing function is used for bonding between metal or polymer surfaces.

[0033] Preferably, the metal is copper foil.

[0034] A fifth aspect is the application of the above-mentioned hot-melt adhesive film with self-repairing function in semiconductor packaging, flexible copper clad laminates, and thermal interface materials.

[0035] The beneficial effects of the present invention are:

[0036] (1) The introduction of multiple effects such as disulfide bonds, flexible Si-O-Si and ether bonds, and hydrogen bonds between molecular chains through molecular structure design can promote the dynamic breaking and re-crosslinking of bonds, so that the broken bonds can be reconnected, thereby giving this type of film material excellent room temperature self-healing ability, and the room temperature self-healing efficiency reaches 85~90%.

[0037] (2) By designing and synthesizing poly(etheramine-siloxane-imide) block copolymers, based on the microphase separation behavior between flexible polyetheramine, polysiloxane and rigid polyimide segments, this type of film has outstanding toughness, with a fracture work of 120~160 MJ·m 3 .

[0038] (3) Block copolymers are prepared using dianhydride monomers containing amide bonds, and amide bonds are introduced into rigid polyimide segments. The abundant hydrogen bonding between amide groups and polyetheramine segments and the siloxane units make this type of adhesive film have excellent adhesion to polymers, metals and other materials. Block copolymers are prepared using dianhydride monomers containing amide bonds, and amide bonds are introduced into rigid polyimide segments. The abundant hydrogen bonding between amide groups and polyetheramine segments and the siloxane units make this type of adhesive film have excellent adhesion to polymers, metals and other materials.

[0039] (4) The amide bonds that provide hydrogen bonding sites in the block copolymer are located between the polyimide segments. Increasing the hydrogen bonding effect between the rigid polyimide segments further improves the cohesive force of the film, which is particularly suitable for hard interface bonding of metals such as copper foil. By increasing the cohesive force, the interface damage phenomenon can be avoided. At room temperature, the bonding strength to the metal (copper foil) surface reaches 9~15MPa, and the bonding strength to the polymer surface reaches 6~10MPa. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0042] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.

[0043] The polyetheramine monomer is an amino-terminated polyoxypropylene ether, and its number average molecular weight is selected from 230, 2000 and 4000, respectively, provided by Sigma-Aldrich Company. The amino-terminated polysiloxane with a number average molecular weight of 2500 is polydimethylsiloxane-bisamino (PDMS-2NH2), provided by Xi'an Qiyue Biotechnology Co., Ltd., 4,4'-diaminodiphenyl disulfide (AD) containing a disulfide bond is provided by Shanghai Aladdin Biochemical Technology Co., Ltd., and the dianhydride N,N'-(2,2-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxy-1,3-dihydroisobenzofuran-5-carboxyamide) (abbreviated as: TA-TFMB) containing an amide unit is provided by Tianjin Zotye New Material Technology Co., Ltd.

[0044] The mechanical properties of the hot-melt adhesive film were tested using a universal material testing machine: the tensile rate was 10 mm / min, the gauge length was 20 mm, and each group of films was measured 10 times to take the average value.

[0045] The bonding properties of the films were tested by lap shear tests with a tensile rate of 50 mm / min.

[0046] The self-healing efficiency of the film is characterized by the change in mechanical strength before and after damage repair.

[0047] Embodiment 1:

[0048] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in NMP solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 2000 were added to the dianhydride solution in sequence, and the solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 45 mol%. The above reaction system was stirred for 18 h under nitrogen atmosphere to obtain a precursor solution; 3 wt% of pyridine was added dropwise to the precursor solution as a catalyst, and the reaction solution was heated to 120 ° C and reacted at this temperature for 5 h, and the reaction system was further heated to 180 ° C and reacted at this temperature for 12 h to finally obtain a viscous film solution. The above solution was coated on a clean glass plate by a knife coating process, placed in a vacuum drying oven, and dried at 120°C for 8 h to obtain a hot-melt adhesive film.

[0049] Embodiment 2:

[0050] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in NMP solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 2000 were added to the dianhydride solution in sequence, and the solid content of the reactants was controlled to be 20 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 20 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 40 mol%. The above reaction system was stirred for 18 h under nitrogen atmosphere to obtain a precursor solution; 3 wt% of pyridine was added dropwise to the precursor solution as a catalyst, and the reaction solution was heated to 120 ° C and reacted at this temperature for 5 h, and the reaction system was further heated to 180 ° C and reacted at this temperature for 12 h to finally obtain a viscous film solution. The above solution was coated on a clean glass plate by a knife coating process, placed in a vacuum drying oven, and dried at 120°C for 8 h to obtain a hot-melt adhesive film.

[0051] Embodiment 3:

[0052] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in NMP solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 2000 were added to the dianhydride solution in sequence, and the solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 30 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 35 mol%. The above reaction system was stirred for 18 h under nitrogen atmosphere to obtain a precursor solution; 3 wt% of pyridine was added dropwise to the precursor solution as a catalyst, and the reaction solution was heated to 120 ° C and reacted at this temperature for 5 h, and the reaction system was further heated to 180 ° C and reacted at this temperature for 12 h to finally obtain a viscous film solution. The above solution was coated on a clean glass plate by a knife coating process, placed in a vacuum drying oven, and dried at 120°C for 8 h to obtain a hot-melt adhesive film.

[0053] Embodiment 4:

[0054] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in NMP solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 230 were added to the dianhydride solution in turn, and the solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 45 mol%. The above reaction system was stirred for 18 h under nitrogen atmosphere to obtain a precursor solution; 3 wt% pyridine was added to the precursor solution as a catalyst, and the reaction solution was heated to 120 ° C and reacted at this temperature for 5 h, and the reaction system was further heated to 180 ° C and reacted at this temperature for 12 h, and finally a viscous film solution was obtained. The above solution was coated on a clean glass plate by a doctor blade process, and placed in a vacuum drying oven, and dried at 120 ° C for 8 h to obtain a hot melt film.

[0055] Embodiment 5:

[0056] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in m-cresol solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 4000 were added to the dianhydride solution in sequence, and the solid content of the reactants was controlled to be 20 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 45 mol%. The above reaction system was stirred for 18 h under nitrogen atmosphere to obtain a precursor solution; 3 wt% pyridine was added dropwise to the precursor solution as a catalyst, and the reaction solution was heated to 120 °C and reacted at this temperature for 5 h, and the reaction system was further heated to 180 °C and reacted at this temperature for 12 h to finally obtain a viscous film solution. The above solution was coated on a clean glass plate by a knife coating process, placed in a vacuum drying oven, and dried at 120°C for 8 h to obtain a hot-melt adhesive film.

[0057] Comparative Example 1:

[0058] Under nitrogen protection, TA-TFMB containing dianhydride of amide unit was dissolved in NMP solvent, and after being fully dissolved, AD and PDMS-2NH2 with a number average molecular weight of 2500 were added to the dianhydride solution in sequence. Unlike Example 1, no diamine containing polyether unit was added to the system. The solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fraction of PDMS-2NH2 was 90 mol%. The remaining reaction conditions were the same as those in Example 1.

[0059] Comparative Example 2:

[0060] Under nitrogen protection, TA-TFMB containing dianhydride of amide unit was dissolved in NMP solvent, and after being fully dissolved, AD and polyetheramine with number average molecular weight of 2000 were added to the dianhydride solution in sequence, except that PDMS-2NH2 was not added to the system in Example 1. The solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fraction of polyetheramine was 90 mol%. The remaining reaction conditions were the same as those in Example 1.

[0061] Comparative Example 3:

[0062] Under nitrogen protection, TA-TFMB containing amide unit dianhydride was dissolved in NMP solvent, and after being fully dissolved, PDMS-2NH2 and polyetheramine with a number average molecular weight of 2000 were added to the dianhydride solution in sequence, and the diamine AD containing disulfide bonds was not added to the system, which was different from Example 1. The solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fractions of PDMS-2NH2 and polyetheramine were both 50 mol%. The remaining reaction conditions were the same as those in Example 1.

[0063] Comparative Example 4:

[0064] Under nitrogen protection, 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride containing amide unit was dissolved in NMP solvent. After being fully dissolved, AD, PDMS-2NH2 with a number average molecular weight of 2500 and polyetheramine with a number average molecular weight of 2000 were added to the dianhydride solution in sequence, and the solid content of the reactants was controlled to be 15 wt%, and the molar ratio of dianhydride to diamine was equal, wherein the molar fraction of AD in the total diamine was 10 mol%, and the molar fractions of PDMS-2NH2 and polyetheramine were both 45 mol%. The remaining reaction conditions were the same as those in Example 1.

[0065] Table 1

[0066]

[0067] The performance comparison of the hot-melt adhesive films prepared in the examples and the comparative examples is shown in Table 1. From this table, it can be seen that Examples 1-5 prepared hot-melt self-healing adhesive films containing polyimide, polyetheramine and polysiloxane segments. Compared with Example 1, no polyether segment was introduced in Comparative Example 1, so the molecular chain was rigid. Although the tensile strength was high, the self-healing efficiency of the film and the bonding strength with the metal copper foil were low due to the lack of hydrogen bonds; in Comparative Example 2, since no polysiloxane segment was introduced, the molecular chain was rigid, but the self-healing efficiency and bonding strength were also lower than those in Example 1; and in Comparative Example 3, no disulfide bond was introduced. Although the molecular chain was flexible, the self-healing ability of the disulfide bond was lacking, and the tensile strength of the film was much lower than that of Example 1, which ultimately led to poor bonding performance; Comparative Example 4 used 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride to replace the TA-TFMB dianhydride containing amide bonds in Example 1, and the molecular chain of the resulting film also lacked hydrogen bonds, so the self-healing efficiency of the film and the bonding strength with the metal copper foil were low.

[0068] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.

Claims

1. A hot-melt adhesive film with self-repairing function, characterized in that: The hot melt adhesive film is prepared from a poly(etheramine-siloxane-imine) block copolymer, which uses a dianhydride monomer containing an amide bond, a diamine containing a polyether unit, a diamine containing a siloxane unit, and a diamine containing a disulfide bond as raw materials, and its molecular chain contains polyetheramine, polysiloxane, and polyimide segments; Wherein, the dianhydride monomer containing an amide bond is N,N'-(2,2-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxyamide), and its structure is shown below: ; The diamine containing polyether units, the diamine containing siloxane units and the diamine containing disulfide bonds are respectively: amino-terminated polyoxypropylene ether, amino-terminated polydimethylsiloxane-bisamino and diamine 4,4'-diaminodiphenyl disulfide containing disulfide bonds, and the corresponding structures are shown below: 、 、 ; The method for preparing the hot-melt adhesive film with self-repairing function specifically includes: S1, dissolving the dianhydride containing amide units in a solvent to obtain a transparent dianhydride solution; S2, gradually adding a diamine containing a polyether unit, a diamine containing a siloxane unit and a diamine containing a disulfide bond unit to the above dianhydride solution, and after all the diamine monomers are dissolved, stirring at room temperature to obtain a precursor solution; S3, adding a catalyst to the precursor solution, and heating it to 100-200°C, reacting at this temperature for 15-20 h, and finally obtaining a film solution; S4, coating the adhesive film solution on the surface of the substrate, and preparing a hot melt adhesive film after drying; Wherein, the solvent includes any one or both of N-methyl-pyrrolidone and m-cresol; Wherein, the catalyst includes any one or both of pyridine and isoquinoline.

2. The hot-melt adhesive film with self-repairing function according to claim 1, characterized in that: The molecular weight of the diamine containing siloxane units is 500-5000, and the molecular weight of the diamine containing polyether units is 230-4000.

3. The hot-melt adhesive film with self-repairing function according to claim 1, characterized in that: The molar content of the polyimide segment in the block copolymer is 10-30 mol%, the polyetheramine and polysiloxane segments are equimolar, and the total molar fraction of the two segments is 70-90 mol%.

4. The hot-melt adhesive film with self-repairing function according to claim 1, characterized in that: The drying process in step S4 refers to a drying process at 120° C. for 8 to 10 hours.

5. Use of the hot-melt adhesive film with self-repairing function as claimed in any one of claims 1 to 4 for bonding between metal or polymer surfaces.

6. Application of the hot-melt adhesive film with self-repairing function as claimed in any one of claims 1 to 4 in semiconductor packaging, flexible copper clad laminates and thermal interface materials.

Citation Information

Patent Citations

  • A self-healing PDMS coating and its preparation method

    CN112592656B

  • Self-repairing TPU (thermoplastic polyurethane) hot melt adhesive film and preparation method thereof

    CN115260967A

  • Self-healing polyimide conductive binder and preparation method thereof, electrode plate and lithium battery

    CN113150277A

  • Preparation method of high-temperature yellowing-resistant colorless transparent polyimide film combined with antioxidant

    CN117264252A